“All people are equal, the fact that one is more black, and the other more white, does not make a difference”: Sexual Pedagogy in Serbia in the Late 19th and Early 20th Century (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This essay explores various cultural and pedagogical discourses of sexuality and sexual conduct. Those discourses were important for the processes of formation of the national state and its “proper” citizens. The analysis tried to prove that many concepts, ideas and knowledge(s) “travelled” from the Western countries to Serbia, where they were appropriated without any changes. To do this, the author has analysed how category of “race” was utilized in the Serbian “conduct books” and women’s magazines. In conclusion, the author pointed out the significance of historical examination of identities, which should help us form more reflexive and critical attitudes towards cultural heritage and traditions.
Keywords: Sexual pedagogy in Serbia; “race”; eugenics; nation’s health; women’s magazine Žena/Woman